Ensinar e aprender funções polinomiais do 2.º grau, no ensino médio: construindo trajetórias - Mesquita, Marcia Aparecida Nunes (2009)
The present work has like objective to investigating how to make constructivist perspectives of learning compatible with the planning of the teaching-learning process, in the particular case of the teaching and of the learning of polynomial functions of the second degree and to analyze the performance of Mathematic teacher with refer to the activities of the planning and development of teaching, in a way compatible with a constructivist perspective of learning. It is based on the Simon s works (1995) on hypothetical learning trajectories (HLT). It is treated of a qualitative research that it involves two Mathematic teachers of a state public school of São Paulo and their work with 62 students in the first year of Junior High School. Initially we elaborated the first version of the hypothetical learning trajectories taking into account the objectives that we selected and the hypotheses of the students' learning that we indicated in agreement with the planning of the teaching. We presented that first version for the teachers to that they were able to through the current knowledge that they possess of their students, to accomplish suggestions, modifications or alterations and this way we elaborate like this together with them the second version of THA, but the teachers presented a passive attitude face to the analysis, not accomplishing any modification in the first version of THA. Afterwards we accompanied the whole development of the trajectory in classroom, we evaluated and we discussed the results of the work with the teachers and we indicated changes in initial THA. The obtained results left ourselves to conclude that became compatible perspectives teaching-learning constructivist with the planning to the we propose tasks involving resolution of problems, use of technologies, interdisciplinary approaches and applications in situations of the daily and in other areas of the knowledge, so that the student could interact and to accomplish experiments, to lift hypotheses, to build resolution strategies, to sketch conjectures, to argue, to relate and to analyze, but we concluded that this doesn't guarantee a learning with constructivist perspectives, its accomplishment depends what manner the teacher will act at the classroom